Integrating Power Bi with Project Control Systems: Enhancing Real-Time Cost Tracking and Visualization in Construction - Rinkesh Gajera (International Journal of Scientific Research in Civil Engineering, 2023)
The importance of this capability is majorly noticed for epidemiologists, who need to understand the way these events might influence rates of transmission of Covid-19, particularly in communities of color facing already the major risks. . This analysis aims to synthesize findings from many sources to provide a major understanding of the way enhancement is done through this integration regarding the real-time visualization, and tracking of cost. Through real-time data visualization, and tracking enhancement by Power BI, the managers of the project can make decisions timely that impact positively the outcomes of the project. The issues regarding data compatibility need to be addressed by the organizations, and adequate training is needed to be provided to ensure the adoption of users. In companies where the occurrence of the integration is noticed, in this regard, 85% of respondents in surveys of the industry reported being able to make more major decisions related to the allocation of budget, and management of resources.